The Effect of Post-extubation Nasal HFOV Support on Extubation Success in Premature Babies in the Neonatal Intensive Care Unit - Mehmet Fatih Deveci; Halil Aslan; Mehmet Kilic; Aydin Bozkaya; Ihsan Yildirim (Haseki Tıp Bülteni)
Aim: Currently, it is recommended to use the nasal intermmittent positive pressure ventilation (NIPPV) mode after extubation. The nasal high-frequency oscillator ventilation (NHFOV) mode, which does not require synchronization, is being investigated to be used as a non-invasive ventilation mode. We aimed to compare the effect of NHOFV and NIPPV used after extubation. Methods: Our study was a randomized controlled study, and according to the power analysis results, 82 patients were included. The study was performed between September 2022 and March 2023. Post-extubation, the patients were randomly assigned to the NHFOV and NIPPV modes. Patients reintubated within the first 72 hours were considered extubation failures. The extubation success rate, demographic and clinical data, and blood gas values of the patients were analyzed. Results: A total of 82 patients were evaluated. No statistically significant difference was found when the extubation success rate was compared in the NHFOV and NIPPV groups (respectively, 80.5% and 73.2%, p=0.432). The partial carbon dioxide pressure was found to be statistically significantly lower in the NHFOV group [respectively, 44.156±12.067 mmHg and 50.634±11.886 mmHg (p=0.017)]. Conclusion: Nasal high-frequency oscillator ventilation is at least as effective as NIPPV for use after extubation. Normalization of blood gas and fewer side effects are promising for routine use.